Menciptakan Ide Kreatif Dalam Perspektif Islam - Erwan Efendi; Siska Tirta Dina; Annisa Zehan Sinaga (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to identify how to create creative ideas in an Islamic perspective. In this modern era, creative ideas are important to study because they are useful in many ways, one of which is from an Islamic perspective. Creative ideas can have a positive influence in an Islamic perspective and have an important role, one of which is in the field of da'wah, creative ideas can create creative da'wah so that it can attract the attention of the da'wah object to the da'wah delivered. In this study using a descriptive qualitative research approach with data collection techniques using literature study techniques. The results of this study are that readers can apply creative ideas in an Islamic perspective, one of which is preaching by using creative ideas and can apply examples of creative preaching. Keywords Creative idea, Islamic Perspective, Qualitative